High-frequency low-dielectric cross-linked silicon-containing polyester imide film and preparation method thereof

CN122897993APending Publication Date: 2026-10-13HANSHAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611312699.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

由于降低介电常数和介电损耗的机制不同,导致同时降低高频介电常数和介电损耗仍具挑战性

Benefits of technology

1、本发明中引入了1,3-双(3-氨基丙基)四甲基二硅氧烷进行共聚,硅氧烷结构中不存在共轭结构,不易发生电子云的流动,有利于抑制分子内和分子间电子转移络合物(Electron transfer complex, ETC)的形成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897993A_ABST
    Figure CN122897993A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of high-frequency low-dielectric crosslinking type silicon-containing polyester imide film. First, a silicon-containing diamine solution is prepared, then hydroquinone-bis(trimellitic acid) ester dianhydride and 1,3,5-tris(4-aminophenoxy) benzene are added into the silicon-containing diamine solution in sequence to react, finally, quinoline is added and stirred uniformly, and then the product is introduced to a clean glass substrate on a casting method after vacuum degassing, and then is placed in a vacuum drying box to gradually experience an imidization process, and then is taken out, cooled to room temperature, and then is placed in water to ultrasonically peel off the film, and the target product is obtained after drying. The high-frequency low-dielectric crosslinking type silicon-containing polyester imide film prepared by the method has low dielectric constant and low dielectric loss characteristics at 10GHz frequency, and has low water absorption, which is beneficial to maintaining the dielectric stability of the film in a humid environment, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic polymer material modification technology, specifically relating to a method for preparing a high-frequency, low-dielectric cross-linked silicon-containing polyesterimide film. Background Technology

[0002] With the rapid development of electronic information technology, the operating frequencies of antenna systems in aviation, aerospace, transportation, and 5G mobile communication technology are shifting towards the gigahertz (GHz) high-frequency band. However, the dissipative nature of electromagnetic waves at GHz frequencies has become the biggest problem limiting microwave transmission efficiency and increasing transmission loss. To improve signal transmission efficiency and reduce signal transmission loss, higher requirements are placed on the dielectric properties of dielectric materials used in high-frequency transmission fields such as mobile phone antennas and millimeter-wave radar antennas, especially the requirement for extremely low dielectric properties at high frequencies, namely, a dielectric constant (Dk) ≤ 3.0 and a dielectric loss (Df) ≤ 0.003 at 10 GHz.

[0003] In the past, the dielectric material used in electronic devices operating at kilohertz (kHz) and megahertz (MHz) frequencies was mainly polyimide film, which has excellent comprehensive properties such as heat resistance and mechanical strength. However, its polar molecular structure leads to significantly higher dielectric constant and dielectric loss at GHz frequencies.

[0004] Recent researchers have prepared polyesterimide films with a highly in-plane oriented structure by introducing 1,4-phenylenediester groups into the molecular structure of polyimide. This structure helps suppress molecular polarization and intramolecular friction under high-frequency applied electric fields, resulting in extremely low high-frequency dielectric loss (only 0.00184 at 10 GHz). However, due to the tight stacking of the molecular structure, the number of polar molecules per unit volume increases, causing the dielectric constant of the polyesterimide film to increase from 3.1 to approximately 3.4 at 10 GHz. Simultaneously reducing both the high-frequency dielectric constant and dielectric loss remains challenging due to the different mechanisms of reducing dielectric constant and dielectric loss. Furthermore, the polyesterimide film has a high water absorption rate (0.77%), while water has a very high high-frequency dielectric constant and dielectric loss, making the dielectric loss of the film prone to significant increases when operating in humid environments. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention proposes a high-frequency, low-dielectric cross-linked silicon-containing polyesterimide film and its preparation method.

[0006] The technical solution of this invention is as follows: In view of the shortcomings of the existing technology, the purpose of this invention is to provide a method for preparing a high-frequency low-dielectric crosslinked silicon-containing polyesterimide film that simultaneously possesses low dielectric constant and low dielectric loss, and has a low water absorption rate.

[0007] The technical solution of this invention is as follows: A method for preparing a high-frequency, low-dielectric crosslinked silicon-containing polyesterimide film includes the following steps: S1. Under ambient humidity below 30%, 0-5℃ and inert atmosphere, the diamine monomers are mixed and dissolved in a polar organic solvent until the diamine is completely dissolved. The mixture is then stirred until homogeneous to obtain a silane-containing diamine solution. The diamine monomers are 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl. S3. Optionally, add crosslinking agent 1,3,5-tris(4-aminophenoxy)benzene to the polyamic acid solution obtained in step S2, and stir for 8-12 hours to obtain a mixed polyamic acid solution. S4. Add quinoline to the polyamic acid solution obtained in step S2 or S3, stir for 2-4 hours, place the solution in a vacuum drying oven for degassing treatment, and after the bubbles are eliminated, guide it onto the substrate for thermal imidization reaction. After the reaction is completed, cool to room temperature, peel off the film, and dry to obtain a high-frequency low-dielectric crosslinked silicon-containing polyester imide film.

[0008] S4. Quinoline is added to the crosslinked polyamic acid solution prepared in step S3. After stirring for 2-4 hours, the solution is placed in a vacuum drying oven for degassing treatment. After the bubbles are eliminated, it is guided onto the substrate for thermal imidization reaction. After the reaction is completed, it is cooled to room temperature, and the film is peeled off and dried to obtain a high-frequency low-dielectric crosslinked silicon-containing polyester imide film.

[0009] Furthermore, the molar ratio of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl is (0-2):(10-8).

[0010] Furthermore, the polar organic solvent is at least one of N-methylpyrrolidone, N,N-dimethylformamide, or N,N-dimethylacetamide.

[0011] Furthermore, in step S3, the molar ratio of the crosslinking agent 1,3,5-tris(4-aminophenoxy)benzene to the dianhydride monomer hydroquinone-bis(trimethicone) ester dianhydride is 0-5%.

[0012] Furthermore, the solid content of the polyamic acid solution obtained in step S2 is 10wt%-20wt%.

[0013] Furthermore, the molar ratio of the total amino group in the diamine monomer and the total anhydride in the dianhydride monomer is 1:1.

[0014] Furthermore, the conditions for the thermal imidization reaction in step S3 are as follows: holding at 60±2℃ for 1.8-2.2 hours, holding at 100±2℃ for 1.8-2.2 hours, holding at 150±2℃ for 0.8-1.2 hours, holding at 200±2℃ for 0.8-1.2 hours, and holding at 250±2℃ for 0.5-1 hours.

[0015] A high-frequency, low-dielectric crosslinked silicon-containing polyesterimide film prepared according to the method described above.

[0016] Furthermore, at a frequency of 10 GHz, the dielectric constant of the film is 2.75-2.97, the dielectric loss is 0.00192-0.00218, and the water absorption rate is 0.38%-0.46%.

[0017] Compared with the prior art, the present invention has at least the following advantages: 1. In this invention, 1,3-bis(3-aminopropyl)tetramethyldisiloxane is introduced for copolymerization. The siloxane structure does not contain a conjugated structure, making it less prone to electron cloud flow, which is beneficial for suppressing the formation of intramolecular and intermolecular electron transfer complexes (ETCs).

[0018] 2. The flexible organosiloxane structure can improve the mobility of molecular chains, reduce the degree of molecular chain packing of polyesterimide, and increase the free volume, thereby effectively reducing the dielectric constant; at the same time, the strong hydrophobicity of the siloxane structure helps to reduce the water absorption rate of polyesterimide, thereby improving its dielectric stability when working in a humid environment.

[0019] 3. Further, 1,3,5-tris(4-aminophenoxy)benzene was used as a crosslinking agent to copolymerize with linear silicon-containing polyester imide, which enhanced the interaction between molecular chains. The spatial confinement effect of the three-dimensional network structure restricted the molecular polarization and intramolecular friction of the molecular chains under the high-frequency external electric field, so that the film maintained its original high-frequency and low dielectric loss characteristics while significantly reducing the dielectric constant and water absorption rate. Attached Figure Description

[0020] To more clearly illustrate the specific embodiments of the present invention, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.

[0021] Figure 1 This is a schematic diagram of the reaction process of the cross-linked silicone-containing polyester imide of the present invention.

[0022] Figure 2 The images show the X-ray diffraction (XRD) patterns of the high-frequency, low-dielectric crosslinked silicon-containing polyesterimide films of the embodiments and comparative examples of the present invention. Detailed Implementation

[0023] The present invention will now be described in further detail. It should be noted that the following specific embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above application content.

[0024] This invention provides a general and / or specific description of the materials and experimental methods used in the experiments. Unless otherwise specified, all experimental or testing methods are conventional methods; all reagents or instruments used, unless otherwise specified, are commercially available conventional products prepared or used using conventional methods.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art.

[0026] In the following examples, hydroquinone-bis(triphenyltriol) dianhydride (TAHQ, CAS No.: 2770-49-2) and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB, CAS No.: 341-58-2) were purchased from Tianjin Zhongtai Technology Co., Ltd.; 1,3-bis(3-aminopropyl)tetramethyldisiloxane (PPA, CAS No.: 2469-55-8), 1,3,5-tris(4-aminophenoxy)benzene (TAPB, CAS No.: 102852-92-6) and quinoline were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; N-methylpyrrolidone (NMP, CAS No.: 872-50-4) was purchased from Jiangsu Qiangsheng Functional Chemical Co., Ltd.; and calcium hydride (CaH2) was purchased from Guangzhou Chemical Reagent Factory.

[0027] Raw material pretreatment: Before use, NMP was mixed with 1% CaH2 (by mass) and stirred for 12 hours, then distilled under reduced pressure at -0.1 MPa to obtain a dry solvent. TFMB and TAPB were placed in a vacuum oven and dried at 60°C for 48 hours. TAHQ was placed in a vacuum oven and dried at 140°C for 48 hours. Glass slides (150mm × 100mm × 1mm) were cleaned with deionized water and then dried in an 80°C oven for 12 hours before use.

[0028] Test Method Description: The dielectric constant and dielectric loss of the thin film at a frequency of 10 GHz were measured using a split-cavity instrument according to GB / T 1409-2006. The water absorption rate of the thin film was measured according to national standard GB / T 1034-2008.

[0029] Example 1: Preparation of silicone-containing polyesterimide films without crosslinking agents S1. Under ambient humidity of 30% and temperature of 0°C, nitrogen gas was introduced into a 100 mL three-necked flask. 4 mmol of TFMB, 1 mmol of PPA, and 21.6 g of dry NMP were added (controlling the solid content of the system to approximately 15 wt%). The TFMB and PPA were stirred mechanically until completely dissolved. Then, 5 mmol of TAHQ was divided into two equal portions, added to the three-necked flask at 30-minute intervals. After the addition was complete, stirring was continued for 8 hours to carry out the polycondensation reaction. Finally, 10 mmol of quinoline was added and stirred for 4 hours to obtain a non-crosslinked silicone-containing polyamic acid solution.

[0030] S2. Place the prepared solution in a vacuum drying oven and, after the air bubbles are eliminated, guide it onto a clean glass substrate. Proceed with the set temperature program, maintaining the temperature at 60±2℃ for 2 hours, 100±2℃ for 2 hours, 150±2℃ for 1 hour, 200±2℃ for 1 hour, and finally at 250±2℃ for 1 hour to perform a thermal imidization reaction. After the reaction is complete, slowly cool the system to room temperature. Then, immerse it in deionized water and sonicate for 10 minutes to peel off the film. Place the film in a 100℃ oven and vacuum dry for 6 hours to obtain a silicone-containing polyester imide film (TAPB content 0%).

[0031] Example 2: Preparation of cross-linked silicone-containing polyesterimide films S1. Under ambient humidity of 30% and temperature of 0°C, nitrogen gas was introduced into a 100 mL three-necked flask. 3.94 mmol of TFMB, 0.985 mmol of PPA, and 21.6 g of dry NMP were added. The mixture was stirred mechanically until completely dissolved. Then, 5 mmol of TAHQ was divided into two equal portions, added to the three-necked flask at 30-minute intervals. After the addition was complete, the mixture was stirred for 8 hours to allow for polycondensation. Next, 0.05 mmol of TAPB was added to the system (to ensure a 1:1 molar ratio of total amino functional groups to total anhydride functional groups participating in the reaction), and the reaction was continued for 12 hours. Finally, 10 mmol of quinoline was added and the mixture was stirred for 4 hours to obtain a cross-linked silicone-containing polyester ammonium acid solution.

[0032] S2. The prepared solution was placed in a vacuum drying oven to remove bubbles. After the bubbles were eliminated, the solution was transferred to a clean glass substrate. The temperature was increased according to the set program, and the solution was held at 60±2℃ for 2 hours, 100±2℃ for 2 hours, 150±2℃ for 1 hour, 200±2℃ for 1 hour, and 250±2℃ for 1 hour to carry out the thermal imidization reaction. After the reaction was complete, the system was slowly cooled to room temperature. The film was then sonicated in deionized water for 10 minutes to peel off. The film was then vacuum dried in a 100℃ oven for 6 hours to obtain a cross-linked silicone-containing polyester imide film (TAPB to TAHQ molar ratio of 1%).

[0033] Example 3: Preparation of cross-linked silicone-containing polyesterimide films The process was essentially the same as in Example 2, except that the amount of crosslinking agent TAPB was increased to 0.15 mmol, and the corresponding amounts of TFMB and PPA were adjusted to 3.82 mmol and 0.955 mmol, respectively, to maintain a 1:1 molar ratio of anhydride to amino group in the reaction system. All other preparation steps, temperature, and time parameters were identical, resulting in a crosslinked silicone-containing polyesterimide film (TAPB to TAHQ molar ratio of 3%).

[0034] Example 4: Preparation of cross-linked silicone-containing polyesterimide films The process was essentially the same as in Example 2, except that the amount of crosslinking agent TAPB was increased to 0.25 mmol, and the corresponding amounts of TFMB and PPA were adjusted to 3.7 mmol and 0.925 mmol, respectively, to maintain a 1:1 molar ratio of anhydride to amino group in the reaction system. All other preparation steps, temperature, and time parameters were identical, resulting in a crosslinked silicone-containing polyesterimide film (TAPB to TAHQ molar ratio of 5%).

[0035] Comparative Example: Preparation of Siloxane-Free Modified Polyesterimide Films The preparation method of the high-frequency, low-dielectric crosslinked silicone polyesterimide film provided in this comparative example is basically the same as that in Example 1, except that PPA is not added in the first step of the preparation, and all PPA components are replaced with TFMB in equal molar amounts (i.e., 5 mmol of TFMB and 5 mmol of TAHQ are used for polycondensation, and no crosslinking agent TAPB is added). The other reaction and curing steps are the same.

[0036] Experimental Results Analysis and Structural Discussion The thin films prepared in this application were subjected to performance tests, and the dielectric constant, dielectric loss and water absorption rate at 10 GHz are shown in Table 1.

[0037] Table 1. Test results of thin film performance in each embodiment and comparative example.

[0038] As shown in Table 1, after introducing the siloxane unit, the dielectric constant of the silicon-containing polyesterimide film (Example 1) significantly decreased from 3.26 of the conventional polyesterimide film (comparative example) to 2.97, while maintaining extremely low dielectric loss. Furthermore, due to the strong hydrophobic effect of the compliant organosiloxane segments, the water absorption rate of the film decreased dramatically from 0.77% to 0.38%, which greatly improves the electrical stability of the film in humid and highly sensitive environments.

[0039] Figure 1 This is a schematic diagram of the reaction process for synthesizing the cross-linked silicon-containing polyester imide obtained in this invention. Figure 2 The XRD patterns of the thin films from Examples 1 to 4 and the comparative examples are shown. Figure 2 The diffraction curves clearly show that the comparative film exhibits a relatively sharp diffraction peak near 2θ of 18° to 20°, indicating a high degree of order in the molecular chain arrangement. However, with the introduction of the crosslinking agent TAPB, the diffraction peak intensities of Example 2 (1% TAPB), Example 3 (3% TAPB), and Example 4 (5% TAPB) gradually broaden and decrease, exhibiting a diffuse peak state. This is mainly due to the introduction of the crosslinking agent disrupting the tightly packed structure of the silicon-containing polyesterimide molecular chains. Although a loose molecular chain packing structure easily leads to molecular polarization and intramolecular friction under a high-frequency applied electric field, thereby increasing dielectric loss, the confinement effect of the crosslinking structure helps to suppress molecular polarization and intramolecular friction. The combined effect of these two factors keeps the dielectric loss of the film within an extremely low range. Simultaneously, the film has a low water absorption rate, indicating that the crosslinked silicon-containing polyesterimide film has significant potential application value in fields such as high-frequency flexible circuit boards.

[0040] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. A method for preparing a high-frequency, low-dielectric cross-linked silicon-containing polyesterimide film, characterized in that, Includes the following steps: S1. Under ambient humidity below 30%, 0-5℃ and inert atmosphere, the diamine monomers are mixed and dissolved in a polar organic solvent until the diamine is completely dissolved. The mixture is then stirred until homogeneous to obtain a silane-containing diamine solution. The diamine monomers are 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl. S2. Add the dianhydride monomer hydroquinone-bis(trimethicone) ester dianhydride to the silane-containing diamine solution in step S1, and stir for 8-12 hours to carry out polycondensation reaction to obtain polyamic acid solution. S3. Optionally, add crosslinking agent 1,3,5-tris(4-aminophenoxy)benzene to the polyamic acid solution obtained in step S2, and stir for 8-12 hours to obtain a mixed polyamic acid solution. S4. Add quinoline to the polyamic acid solution obtained in step S2 or S3, stir for 2-4 hours, place the solution in a vacuum drying oven for degassing treatment, and after the bubbles are eliminated, guide it onto the substrate for thermal imidization reaction. After the reaction is completed, cool to room temperature, peel off the film, and dry to obtain a high-frequency low-dielectric crosslinked silicon-containing polyester imide film.

2. The preparation method according to claim 1, characterized in that, The molar ratio of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl is (0-2):(10-8).

3. The preparation method according to claim 1, characterized in that, The polar organic solvent is at least one of N-methylpyrrolidone, N,N-dimethylformamide, or N,N-dimethylacetamide.

4. The preparation method according to claim 1, characterized in that, In step S3, the molar ratio of the crosslinking agent 1,3,5-tris(4-aminophenoxy)benzene to the dianhydride monomer hydroquinone-bis(trimethicone) ester dianhydride is 0-5%.

5. The preparation method according to claim 1, characterized in that, The solid content of the polyamic acid solution obtained in step S2 is 10wt%-20wt%.

6. The preparation method according to claim 1, characterized in that, The molar ratio of the total amino group in the diamine monomer and the total anhydride in the dianhydride monomer is 1:

1.

7. The preparation method according to claim 1, characterized in that, The conditions for the thermal imidization reaction in step S3 are as follows: hold at 60±2℃ for 1.8-2.2 hours, at 100±2℃ for 1.8-2.2 hours, at 150±2℃ for 0.8-1.2 hours, at 200±2℃ for 0.8-1.2 hours, and at 250±2℃ for 0.5-1 hours.

8. A high-frequency low-dielectric crosslinked silicon-containing polyesterimide film prepared by the method according to any one of claims 1-7.

9. The high-frequency, low-dielectric cross-linked silicon-containing polyesterimide film according to claim 8, characterized in that, At a frequency of 10 GHz, the dielectric constant of the film is 2.75-2.97, the dielectric loss is 0.00192-0.00218, and the water absorption rate is 0.38%-0.46%.